Agricultural Management Options for Climate Variability and Change: Microirrigation - Lincoln Zotarelli; Clyde Fraisse; Daniel Dourte (EDIS, 2012)
Microirrigation is the slow, frequent application of water directly to relatively small areas adjacent to individual plants through emitters placed along a water delivery line. A leading advantage of microirrigation is that evaporation that does not contribute to plant growth happens much less than with sprinkler irrigation. This 5-page fact sheet was written by Lincoln Zotarelli, Clyde Fraisse, and Daniel Dourte, and published by the UF Department of Horticultural Sciences, July 2012.